SINDROMA TURNER (SINDROMA BONNEVIE-URLICH) - Wiyasa, Arsana; Pudjiastuti, Retno (Fakultas Kedokteran Universitas Brawijaya, 2003)
It was reported a case of Turner syndrome of fifteen years old girl who complain have not started menses. Physical examination included short stature, shield chest with wide spaced nipples and secondary sex was absent. External genitalia was normally, internal genitalia was found hipoplasia of uterine. Laboratory examination showed low estrogen, high FSH and LHand normothyroid. Karyotype was 45, X, USG examination showed there was no development of uterine. X-ray of extremity showed that epiphiseal line has not closed, bone age used of method of Todd (manus), linear growth (femur, tibia, fibula), quantity of growth (femur, tibia) accordingly 11-12 years. Expectant to increase her height was low because growth hormon preparation was difficult to find and the price was not attainable by the pasien. Just low dose ethinil estradiol have been given for pasien until bone age more than 12 years when epiphiseal line have been closed and will continue with full dose ethinil estradiol until post menopause. Key words:Turner syndrome, growth hormon, ethinil estradiol,epiphiseal line